(3eNJUQ ef cJH GdSjGSI eeG jMJGL Edjg Gdedhcs
(3ChdgG (B:s
(3ai aVd GdNdGaI hMceJgG bGd UGMH GdCMcGe GdSdWGfjI cGeGeI ehVhYI dNdGaI GdfHhI ai MQGSI GdOjf hSjGSI GdOfjG s
(3BNQgG (B:s
(3GdLjT CYhGf jJcdage GdeGd (B: (3GdeGd QRb JLeYg GdQYjI GdYOd NGdhb hgh bhGe GdYGde GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3RGhjI JfZdH GdeZQH(B) (35) s
Keywords: (3GdSjGSI hGdGLJeGYs